Response of rice to different organic and inorganic nutrient sources at Parwanipur, Bara district of Nepal - Devkota, Sabina; Panthi, Sharan; Shrestha, Jiban (Journal of Agriculture and Natural Resources, 2019)
In order to reach an optimum and sustainable production, growers must know the fertilizing nutrient sources and their application rates. The present study aimed to determine the effect of different organic and inorganic source of fertilizers on growth and performance of rice. A field experiment was conducted at Regional Agriculture Research Station, Parwanipur, Bara, Nepal during summer season of 2013. Rice variety ‘Hardinath 1’ was used in these experiments. Treatments included a combination of organic and inorganic nutrients at eight rates (control, recommended dose of NPK, ½ NPK+FYM 10 t ha-1, ½ NPK+20 cm crop residue, ½ NPK+Chicken manure 10 t ha-1, ½ NPK+Vermicompost 10 t ha-1, FYM 10 t ha-1 and FYM 20 t ha-1).The experiments were laid out in Randomized Complete Block Design with four replications. Treatments produced significant results for plant height, number of tillers per square meter, panicle length and grain yield but thousands grains weight was insignificant. Result showed that application of half of recommended N: P2O5: K2O from the inorganic fertilizer sources along with soil incorporation of 20 cm crop residue produced significantly higher value for plant height, number of tillers per square meter, panicle length and Grain yield. Treatments did not produce significant effect on after harvest soil properties: pH, organic matter, nitrogen, phosphorus and potassium content.